Systemic sarcoidosis reactions as a result of tumour necrosis factor‐alpha treatment for patients with psoriasis. (9th July 2021) - Bewley, A. P.; Maleki, S.
Summary: The high efficacy and tolerability of biological therapies such as anti‐tumour necrosis factor‐alpha (TNF‐α) have transformed outcomes for many inflammatory conditions. Conversely, a wide range of paradoxical reactions, including pulmonary, renal and ocular sarcoidosis secondary to TNF‐α blocking agents in patients with severe psoriasis, has been reported. Sarcoid‐like granulomatosis is one of these reactions, which may affect the pulmonary and cutaneous systems. Renal and ocular sarcoidosis, however, are less frequent and have unknown consequences. In this report, we present two cases of anti‐TNF‐α‐induced sarcoidosis involving the pulmonary and renal systems.